Pengaruh Disiplin Kerja dan Usia Terhadap Kinerja Karyawan Pemanen di Afdeling 1 PT Perkebunan Nusantara IV Regional II Kebun Tinjowan - Ryan Darmawan Dalimunthe; Hamzah Manurung (Universitas Medan Area, 2026)
This study aims to analyze the influence of work discipline and age on the performance of harvesters at Afdeling 1 of PT Perkebunan Nusantara IV Regional II Tinjowan Plantation. The method used was quantitative descriptive, with a population of 21 harvesters, all of whom were included in the sample using a saturated sampling technique. Data were collected through a questionnaire using a Likert scale, observation, and documentation, then analyzed using multiple linear regression with the aid of SPSS version 25. The results indicate that, simultaneously, work discipline and age have a positive and significant effect on employee performance. Partially, work discipline significantly affects performance, while age also significantly affects performance. The results of the coefficient of determination analysis indicate that work discipline and age account for 49% of employee performance, while the remainder is influenced by other factors outside the scope of this study. Thus, improving work discipline and managing the workforce based on productive age can enhance the performance of harvesters.